Inflammatory Cytokine Response in Dengue Infected Female of Reproductive Age: Insight with Reference to a Pregnant Case - Rauniyar, Ramanuj; Manandhar, Binod; Jha, Satish Chandra; Joshi, Indu Bikram; Chalise, Bimal Sharma; Wallace, Paul K; Telford, William; Manandhar, Krishna Das (Journal of Institute of Science and Technology, 2024)
Dengue treatment and management is challenging during the epidemic especially among the risk groups and to mitigate the risks becomes even more complicated in absence of specific medicine and vaccines. Till date, there are no specific research endeavours in Nepal focusing on pregnant women with dengue and there is evident gap in research concerning the treatment of pregnant women due to overlapping clinical and hematological manifestations with physiological changes of gestation. The study comprises clinically diagnosed one dengue positive pregnant female, five female patients with dengue in Sukraraj Tropical and Infectious Disease Hospital (STIDH), Kathmandu and five healthy volunteers of same reproductive age. The study investigates six different inflammatory cytokines; IL-1β, IL-6, IL-8, IL-10, IL-12p70 and TNF levels in plasma and were quantified using Cytometric Bead Array. The Cytokine profiles and blood parameters were statistically analyzed using confidence intervals of 93.75% as permitted by sample size and visualized with box and whisker plot with a highlighted pregnant case. The study shows IL-6 and IL-10 levels are elevated on dengue cases as compared to healthy while TNF and IL-12p70 levels are elevated exceeding the upper limit of the acute dengue cases in the pregnant subject, underscoring heightened inflammatory activity during synchronous pregnancy and dengue infection. There were significant reductions in hemoglobin and leukocyte counts in the pregnant dengue case compared to non-pregnant. These findings suggest cytokine modulations occur during pregnancy and underscores the importance of these patterns provide insight into targeted therapeutic and diagnostic strategies to mitigate the risks for vulnerable population.